2013
DOI: 10.7205/milmed-d-12-00079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Framingham Cardiovascular Disease Risk Among Militaries in the Kingdom of Saudi Arabia

Abstract: The prevalence of CVD risk factors is high among militaries in the Kingdom of Saudi Arabia, with an associated high 10-year CVD Framingham risk. The military health services must implement intervention programs to reduce these risks, with follow-up of the participants with identified CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
14
1
1
Order By: Relevance
“…A detailed methodology of the main survey has previously been reported. [ 21 ] The study used a descriptive cross-sectional design. The sample consisted of 10,500 military personnel of any rank serving in the Saudi Armed Forces during the time of the study.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed methodology of the main survey has previously been reported. [ 21 ] The study used a descriptive cross-sectional design. The sample consisted of 10,500 military personnel of any rank serving in the Saudi Armed Forces during the time of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The Framingham heart study, conducted by Al Humaidi, in Abha province, KSA, have reported a mean risk of 8.9% for developing coronary artery disease [29]. Another recent study that was conducted among the military population, which were expected to have higher fitness level, revealed that one-tenth of the participants had a 10-year CVD risk of ≥10%, with a mean risk of 4.5% [30]. However, the probability of 10 year-CVD risk based on the FRS and its association with sedentary life style in the general Saudi population remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This is believed to result from multiple factors including rapid socioeconomic development, lifestyle changes, urbanization and ageing [5 -7]. The prevalence of CVD in the Kingdom of Saudi Arabia has been reported to be at 5% [6]. A 2014 National Survey revealed that 15.2% of Saudis are hypertensive and 40% were borderline hypertensive [8].…”
Section: Introductionmentioning
confidence: 99%